Community Aspect of Sustainability Assessment in Malaysian Public Research Universities - Saadatian, Omidreza (2011)
Campuses are small urban areas, which have the characteristic of an active city. As much as Sustainable Development is important for a city, it is important for a campus, too. In order to maintain Sustainability in Higher Education, goal and priority have to be set and the progress should be assessed. In the realm of Sustainable Development several approaches exist that assess Sustainable Development in microscope (building) and mega scope (city) level. However, in Malaysia, there is yet any assessment approach inclusive of indicators in local level (campus). In order to address this problem, evaluating the different Sustainability in Higher Education assessment approaches and identifying the relevant one for Malaysia, identifying Sustainability in Higher Education assessment indicators in community aspect for Malaysia Higher Education Institution, and formulating the indicators of Sustainability in Higher Education considering Malaysian experts opinions have been set as the objectives of the study. Hence, an exploratory method utilizing archival method and content analysis was employed to find out various international Sustainability in Higher Education assessment approaches and their strength and weakness. The archival technique found out 17 popular assessment approaches such as University Leader for Sustainable Future (ULSF) questionnaire tool; Pen State Indicator Report; Campus Sustainability Assessment Framework; Sustainability Tracking and Assessment Rating System. In this regard, the 17 approaches were content analysed to investigate theirs strength and weakness. For validating the content analysis, an interview technique was used to set a suitable Sustainability in Higher Education assessment approach for Malaysia Higher Educational Institution. However, it is necessary to localize this approach based on the needs of Malaysian Higher Education Institution. Therefore, a case study strategy was employed which embedded four public university campuses that were the oldest, the most popular and housed the biggest number of students as the study base. In this regards various techniques such as observation, interview as the relevant techniques of case study strategy were employed to identify the specific challenges of Malaysian Higher Educational Institution. Finally, the interview and questionnaire survey were used to adapt to and formulate the relevant indicators of Sustainability in Higher Education for Malaysian Higher Educational Institution. Campus Sustainability Assessment Framework (CSAF) was found as a suitable approach to be taken as the assessment base approach for Malaysia Higher Educational Institution. Besides three major challenges were identified as the obstacles of Sustainability in Higher Education in Malaysia; namely, ethnic group polarization, imbalance gender distribution, and poor command of English. Finally, the survey and final interview led the research to modify a set of new formulated indicators for Malaysia context. The proposed approach, in a format of formulates indicators, has not only taken Malaysia Higher Educational Institution challenges and Malaysian expert‟s opinions but also has investigated the relevancy of students, academicians and staff, separately, in each indicator. Based on the research findings and results, comparative monitoring of the Sustainability in Higher Education in terms of community will be possible to be accomplished and the shortcoming of Sustainability in Higher Education will be distinguished. In addition, monitoring the campuses and implementing new sustainable initiative, is the first step towards achieving the goal of Malaysia vision 2020. Moreover, the universities can have the same platform to compete in terms of Sustainability in Higher Education and use their rivalry to redress the ongoing existing challenges.